2020
DOI: 10.1177/0169796x19898964
|View full text |Cite
|
Sign up to set email alerts
|

External Financial Flows and GDP Growth in Kosovo

Abstract: This article examines the impact that external financial flows have on gross domestic product (GDP) growth in a new, small, and open economy—the Republic of Kosovo. Remittances, foreign direct investment (FDI), foreign debt, and net exports may affect GDP in different ways. In the context of a new, small, and open economy, these factors can be important determinants of economic development. This article examines the direct effect of these factors on economic development as represented by GDP growth in Kosovo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Hence, many debates included some open aspects in the empirical methods. In open economies, remittances tend to be the major deriving force of growth from the financial inflow components (Govori and Fejzullahu 2020) and (Kumar 2013) The size of the Economy also makes difference. Financial inflows tend to have positive effects on growth in small economies, especially in the short-term (Kumar 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, many debates included some open aspects in the empirical methods. In open economies, remittances tend to be the major deriving force of growth from the financial inflow components (Govori and Fejzullahu 2020) and (Kumar 2013) The size of the Economy also makes difference. Financial inflows tend to have positive effects on growth in small economies, especially in the short-term (Kumar 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that no unique investment model could be identified and that types of models differ from one country to another. Govori and Fejzullahu (2020) examined the impact of external financial flows (i.e., foreign direct investment, external debt, net exports) on GDP growth in Kosovo and concluded that such financial flows generally increased the number of jobs and mitigated unemployment and dependence on imports. Maryam and Mittal (2019) studied the link between financial direct investment flows and the determinants of GDP, such as trade liberalization, exchange rate, gross capital formation and infrastructure, in the case of BRICS countries.…”
Section: Brief Taxonomy Regarding the Impact Of Financial Direct Inve...mentioning
confidence: 99%
“…Moreover, innumerable research has been widely discovered in several macroeconomy variables that affect FDI in various countries. Such as BRICS countries by Maryam and Mittal (2020), Select South Asian Countries by Sahoo and Sethi (2020), in Organisation for Economic Co-operation and Development (OECD) by (Cieślik, 2019), in Kosovo by Govori and Fejzullahu (2020), in Greece by Tsitouras et al (2020), in 23 countries by Canh et al (2019), German by Camarero et al (2019), India by Arul Provin Binny and Morarji (2019) and etcetera. Whereas, there still limited research that analyzes the specific variables which influence the FDI in OIC countries.…”
Section: Graph 1 Foreign Direct Investment Inward Flow In Oic Countries (Us$ Million)mentioning
confidence: 99%